Analisis Efektivitas dan Kontribusi Penerimaan Retribusi Jasa Usaha terhadap PAD Kabupaten Bandung - SP, Ivan Gumilar (Universitas Brawijaya, Indonesia, 2016)
Regional retribution, as well as regional taxes is one of the regional revenue is expected to be one source of financing governance and regional development, to improve and equalize the welfare of the society. So,this study was conducted to determine the effectiveness and contribution of charges for services to regional revenue Bandung District in 2010-2013. The results showed that many types of the retribution of charges for services that are less effective and did not contribute to PAD Bandung District. Including retribution of flats, rental of regional government'sland use, recreation areas, sport areas, and the sale of the production business. While the types of the retribution of charges for services which contribute only rental of heavy equipment from the department of Bina Marga and station services.